2022
DOI: 10.1007/s13738-022-02595-8
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the antimicrobial performance based on new fused spirothiazolidine framework analogs

Abstract: New spiro[cyclohexane-1,2'-thiazolo[4,5-b]pyridine derivatives (3–23) were investigated. Then there is in vitro antimicrobial potency against possible organisms Staphylococcus aurous ATCC-47,077, Bacillus cereus ATCC-12228, Escherichia coli ATCC-25922, Salmonella typhiATCC-15566, and Candida albicans ATCC-10231 were tested utilizing commercially available antibiotics ampicillin as a reference drug. A preliminary antimicrobial test represented that derivatives: (Aldoses) 3'-(4-fluorophenyl)-5'-(methyleneamino)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Briefly, the MW of all the synthesized spirooxindole‐oxofuran was less than 500 Daltons, whereas the number of HBDs and HBAs for 4 a – d was recorded at the desirable thresholds of less than 5 and 10, respectively. The numbers of rotatable bonds were also found to be 4 or 5 for 4 a – d falling within the permissible threshold of less than 5 [12,13] …”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Briefly, the MW of all the synthesized spirooxindole‐oxofuran was less than 500 Daltons, whereas the number of HBDs and HBAs for 4 a – d was recorded at the desirable thresholds of less than 5 and 10, respectively. The numbers of rotatable bonds were also found to be 4 or 5 for 4 a – d falling within the permissible threshold of less than 5 [12,13] …”
Section: Resultsmentioning
confidence: 80%
“…The numbers of rotatable bonds were also found to be 4 or 5 for 4 a-d falling within the permissible threshold of less than 5. [12,13] Considering the potential of hydrophilicity in drug distribution pattern, analysis of Log P has widely been used to assess the permeability of a drug candidate, whereas, the TPSA is used as the measure of the polarity and trans-membrane transport of compounds. [14,15] Our results showed that all the synthesized spirooxindole-oxofuran ( 4 a-d These values for the TPSA for all the newly synthesized spirooxindole-oxofuran (4 a-d) were similar to that reported in the previously published reports.These properties signify the fact that the newly synthesized spirooxindole-oxofuran qualify Scheme 1.…”
Section: Computational Chemistryspirooxindole-oxofurans (4 A-d) Exert...mentioning
confidence: 99%
“…It can be seen from the results in Table 1 and Table 2 and Figure 4 that the biological activity of P16 toward most bacteria and candida strains was high. This may be related to the fused pyridine ring with spirothiazolidine in the chemical structure of P16 , which this likely played an important role in enhancing the biological activity [ 37 ]. Moreover, nucleophilic groups (NH 2 , CN) and the presence of electron-donating groups (CH 3 , hexadecyl) likely also resulted in the high degree of biological activity of P16 [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may be related to the fused pyridine ring with spirothiazolidine in the chemical structure of P16 , which this likely played an important role in enhancing the biological activity [ 37 ]. Moreover, nucleophilic groups (NH 2 , CN) and the presence of electron-donating groups (CH 3 , hexadecyl) likely also resulted in the high degree of biological activity of P16 [ 37 ]. These results indicate that P16 favored the dispersion of AgNPs and improved their biocompatibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation